THE USING OF INSTAGRAM APPLICATION AS MEDIUM TO IMPROVE READING COMPEHENSION - Eli Sutari; Ikhsanudin; Luwandi Suhartono (JEELL (Journal of English Education, Linguistics and Literature), 2025)
This study explored the use of the Instagram application as a medium to improve reading comprehension among eleventh-grade student at SMA Santun Untan Pontianak. Using a narrative inquiry approach, the research focused on students' experiences with Instagram and its impact on student reading skills. Data were collected through in-depth interviews and analyzed thematically. Findings indicated that student were initially motivated by curiosity and peer influence. Student’s experiences with Instagram opened up opportunities for creative expression, inspiration, and ultimately improved reading comprehension skills.